Direct desorption/ionization of analytes by microwave plasma torch for ambient mass spectrometric analysis. (22nd May 2013) - Zhang, Tiqiang; Zhou, Wei; Jin, Wei; Zhou, Jianguang; Handberg, Eric; Zhu, Zhiqiang; Chen, Huanwen; Jin, Qinhan
Abstract : Ambient ionization is the new revolution in mass spectrometry (MS). A microwave plasma produced by a microwave plasma torch (MPT) at atmospheric pressure was directly used for ambient mass spectrometric analysis. H3 O + and NH4 + and their water clusters from the background are formed and create protonated molecules and ammoniated molecules of the analytes. In the full‐scan mass spectra, both the quasi‐molecular ions of the analytes and their characteristic ionic fragments are obtained and provide evidence of the analyte. The successful detection of active compounds in both medicine and garlic proves that MPT has the efficient desorption/ionization capability to analyze solid samples. The obtained decay curve of nicotine in exhaled breath indicates that MPT‐MS is a useful tool for monitoring gas samples in real time. These results showed that the MPT, with the advantages of stable plasma, minimal optimization, easy, solvent‐free operation, and no pretreatment, is another potential technique for ambient MS. Copyright © 2013 John Wiley & Sons, Ltd.